Reliability of a digital weighing scale relative to the Nintendo Wii in measuring limb load asymmetry. - Kuma, Senthil N. S.; Joseph, Leonard H.; Omar, Baharudin; Sulaiman, Riza; Nor, Hamdan M. Y.; Htwe, Ohnmar; Hamidun, Nursalbiyah; Broadbent, Suzanne (International Journal of Therapy & Rehabilitation, 2015)
Background/Aims: Limb load asymmetry (LLA) is common in clinical conditions related to the lower limbs such as degenerative joint disease, soft tissue injuries, joint replacements, amputations and stroke. However, the measurement of LLA is limited in clinical practice as the equipment used is expensive and not readily available in most health care settings. The digital weighing scale is proposed as an inexpensive alternative method of measuring LLA and the objective of this study was to investigate the reliability and accuracy of a digital weighing scale relative to the Nintendo Wii in measuring limb load asymmetry during static standing. Methods: Twenty-four participants (12 participants with knee osteoarthritis (OA) and 12 healthy participants) were recruited through convenient sampling from a public university teaching hospital. The participants were required to perform a quiet standing task during the measurement of LLA. The measurements were taken over three trials during both eyes-open (EO) and eyes-closed (EC) resting conditions. LLA was measured in kilograms and computed with a symmetry index. Intra-class correlation coefficient (ICC) (3, 1) analysis, standard error of measurement and coefficient of variation were performed to assess reliability. The Bland-Altman plot was used to test the degree of agreement between digital weighing scales and the Nintendo Wii. Results: The digital weighing scale showed an excellent reliability of 0.983 and 0.988 in EC and EO conditions, respectively. The Bland-Altman plot showed good agreement between digital weighing scales and the Nintendo Wii in measuring LLA. Conclusions: The digital weighing scale is a reliable tool to measure LLA and has excellent potential to be used in clinical settings.